The role of customer readiness and participation in non-technology-based service delivery. Issue 6 (10th September 2018) - Poushneh, Atieh; Vasquez-Parraga, Arturo Z.
Abstract : Purpose: This study aims to answer the following question: How can customer readiness be instrumental in non-technology-based service delivery? Design/methodology/approach: Using a field study, this research examines the role of customer readiness in customer participation in non-technology-based service delivery and its indirect effects on such customer outcomes as perceived service quality, customer satisfaction and customer willingness to recommend. Findings: The results show that customer readiness is a second-order construct. It has a significant impact on customer participation in service delivery, which in turn impacts three key service outcomes: customer perceived service quality, customer satisfaction and customer willingness to recommend. Four factors influencing customer readiness (consumer previous experience, consumer desire for control, consumer perceived risk and customer organizational socialization) are also empirically evaluated. Research limitations/implications: Some limitations of the study are related to sample size and use of a type of services. The research tested 13 hypotheses with a limited sample size in one context. A better representation of the population and a more generalizable outcome require more representative samples and studies in various contexts such as banking, hotel services or health care services. This study demonstrated the importance of customer readiness for effective participation in non-technology-based service delivery; it does not address the impact of customer readiness on participation in the context of technology-based services. Future research may also shed light on when and why customers choose technology-based services versus non-technology-based services. Practical implications: Effective customer participation in service delivery can, and should, benefit from boosting customer readiness. Originality/value: This research shows the impact of customer readiness on non-technology-based service delivery, more specifically, the impact of customer readiness on customer participation in this type of service delivery. Customer readiness has been found to be beneficial in the provision of technology-based services; yet, its role in the provision of non-technology-based services has not been thoroughly evaluated.